Effect of UV irradiation on the proportion of organic chloramines in total chlorine in subsequent chlorination. (February 2016) - Zhang, Tian-Yang; Lin, Yi-Li; Xu, Bin; Xia, Sheng-Ji; Tian, Fu-Xiang; Gao, Nai-Yun
Abstract: This study investigated the changes of chlorine species and proportion of organic chloramines during the chlorination process after UV irradiation pretreatment in drinking water. It was found that the UV pretreatment could enhance the percentage of organic chloramines by increasing free chlorine consumption in the chlorination of raw waters. The percentage of organic chloramines in total chlorine increased with UV intensity and irradiation time in raw waters. However, for the humic acid synthesized water, the percentage of organic chloramines increased first and then decreased with the increase of UV irradiation time. The value of SUVA declined in both raw and humic acid synthesized waters over the UV irradiation time, which indicated that the decomposition of aromatic organic matter by UV could be a contributor to the increase of free chlorine consumption and organic chloramine proportion. The percentage of organic chloramines during chlorination of raw waters after 30-min UV irradiation pretreatment varied from 20.2% to 41.8%. Total chlorine decreased obviously with the increase of nitrate concentration, but the percentage of organic chloramines increased and was linearly correlated to nitrate concentration. Graphical abstract: Highlights: UV enhanced organic chloramine proportion in total chlorine of raw waters. Humic substance after UV irradiation contributed to organic chloramine proportion. SUVA declined in both raw and humic acid synthesized waters over irradiation time. Nitrate increased organic chloramine proportion in UV/chlorine process.